2014
DOI: 10.1007/s00586-014-3470-0
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter study on accuracy and complications of freehand placement of cervical pedicle screws under lateral fluoroscopy in different pathological conditions: CT-based evaluation of more than 1,000 screws

Abstract: Malposition rate of PS placement in the cervical spine by freehand technique was high in rheumatoid patients even when being performed by experienced spine surgeons. Any guidance tools including navigation systems are recommended for placement of cervical PSs in patients with RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
80
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(88 citation statements)
references
References 26 publications
(39 reference statements)
3
80
0
5
Order By: Relevance
“…The percentage of CPS misplacement varies from 2.5 to 29.1 % in the literature (Table 3) [3, 16, 20, 2736]. In the present study, 6.4 % of CPS misplacement of grade 1–3 in the first period and 2.9 % in the second period were recognized.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…The percentage of CPS misplacement varies from 2.5 to 29.1 % in the literature (Table 3) [3, 16, 20, 2736]. In the present study, 6.4 % of CPS misplacement of grade 1–3 in the first period and 2.9 % in the second period were recognized.…”
Section: Discussionsupporting
confidence: 54%
“…Neo et al reported that the rate of malposition was 29 % in patients with degenerative conditions [20]. Hojo et al reported that the overall rate of malposition was 158 of 1065 inserted screws (14.8 %) in their retrospective multicenter study of free-hand insertion technique with fluoroscopy [16]. Even with a preoperative 3D CT-based navigation system, there is always a risk of misplacement of CPS that may result in significant neural or vascular complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Average midcervical (C3-5) alpha-angles was 52 degrees (range 43 to 62) in MICEPS fixation group, and 39 degrees (range 19 to 55) in conventional cervical pedicle screw group. When displaced, cervical pedicle screws tend to perforate laterally 6,11,12) , and a lateral perforation that causes VA injury is a critical complication of cervical pedicle screw insertion [10][11][12] . Yukawa et al reported that 72% of misplaced screws deviate laterally 11) .…”
Section: Discussionmentioning
confidence: 99%
“…Although cervical pedicle screw fixation is essential for reconstruction in spinal disor-ders 3,[6][7][8][9][10] , its use also presents a risk for vertebral artery (VA) injury 11,12) . To avoid lateral misplacement of midcervical pedicle screws, Tokioka developed a method known as minimally invasive cervical pedicle screw (MICEPS) fixation via the posterolateral approach 13) .…”
Section: Introductionmentioning
confidence: 99%